2020
DOI: 10.3389/fcimb.2020.586507
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Three Porcine Acinetobacter towneri Strains Co-Harboring tet(X3) and blaOXA-58

Abstract: Tigecycline is the antibiotic of last resort for the treatment of extensively drug-resistant bacterial infections, mainly those of multidrug-resistant Gram-negative bacteria. The plasmid-mediated tet(X3) gene has recently been described in various pathogens that are resistant to tigecycline. We report three tigecycline-resistant Acinetobacter towneri strains isolated from porcine faeces in China, which all contained the tet(X3)-harboring plasmids. A broth microdilution method was used to examine the antimicrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
1
10
0
1
Order By: Relevance
“…Hence, the emergence of tet(X4)-positive common plasmids with high mobility might cause an increasing prevalence of tet(X4). In addition, we found that all tet(X)-positive plasmids in Acinetobacter in the chicken farm had no ability of horizontal transfer, which is consistent with the previous reports (Cui et al, 2020;Ma et al, 2020;Wang et al, 2020). Genetic structure analysis found that those tet(X) genes in plasmids harbored by Acinetobacter were adjacent to ISCR2, indicating that ISCR2-mediated mobilization of tet(X) also deserved concerns among bacteria of different genus.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Hence, the emergence of tet(X4)-positive common plasmids with high mobility might cause an increasing prevalence of tet(X4). In addition, we found that all tet(X)-positive plasmids in Acinetobacter in the chicken farm had no ability of horizontal transfer, which is consistent with the previous reports (Cui et al, 2020;Ma et al, 2020;Wang et al, 2020). Genetic structure analysis found that those tet(X) genes in plasmids harbored by Acinetobacter were adjacent to ISCR2, indicating that ISCR2-mediated mobilization of tet(X) also deserved concerns among bacteria of different genus.…”
Section: Discussionsupporting
confidence: 91%
“…What is noteworthy is that a carbapenemase gene bla OXA−58 was found in the tet(X6)-bearing plasmid. Although many plasmids co-harboring tet(X3) and bla OXA−58 have been reported in other species of Acinetobacter (Cui et al, 2020;Ma et al, 2020), tet(X6)-and bla OXA−58bearing plasmid was rarely reported (Zheng et al, 2020). As a clinically critical opportunistic pathogen, the emergence of carbapenem-and tigecycline-resistant A. baumannii poses a great threat to public health.…”
Section: The Genetic Contexts Of Tet(x) Variantsmentioning
confidence: 99%
“…Ecological niches in which plasmid-encoded TIG resistance tet (X) genes have been detected are shown in Table 1 . Clearly, there is increasing evidence of plasmid-encoded TIG resistance tet (X) genes reported in countries across Europe, Asia, United States, South America, and Africa involving humans, food animals, including chickens, pigs, ducks, pigeons, geese, and cattle, as well as companion animals, food animal products (meats), aquaculture and environment such as soil, livestock-farm water, wastewaters, sewages, and wildlife as reservoirs of MTR ( Bai et al, 2019 ; Chen et al, 2019a , b , 2020 , 2021 ; He et al, 2019 ; Sun C. et al, 2019 , 2020 ; Sun J. et al, 2019 ; Cao et al, 2020 ; Cui et al, 2020 , 2021b ; Ding et al, 2020 ; Du et al, 2020 ; He T. et al, 2020 ; Li et al, 2020 , 2021f ; Ma et al, 2020 ; Pan et al, 2020 ; Ruan et al, 2020 ; Song et al, 2020 ; Wang et al, 2020a , b ; Zhang et al, 2020b , 2021 ; Zheng et al, 2020 ; Cheng et al, 2021a , b ; Feng et al, 2021 ; Hirabayashi et al, 2021a , b ; Hsieh et al, 2021 ; Li et al, 2021e , f ; Lu et al, 2021 ; Marathe et al, 2021 ; Martelli et al, 2021 ; Mohsin et al, 2021 ; Soliman et al, 2021 ; Sun et al, 2021a , b ; Tang et al, 2021 ; Wang et al, 2021f , g ; Xu et al, 2021 ; Yu Y. et al, 2021 ; Wu et al, 2022 ; Zhai et al, 2022 ). We further demonstrate this, through the specific reservoirs in which plasmid-borne transmissible tet (X) and tmexCD-toprJ genes have been detected as shown in Table 2 .…”
Section: Distribution Reservoirs and Traits Of Mobile Tigecycline Res...mentioning
confidence: 99%
“…Acinetobacter towneri, belonging to the genus Acinetobacter whose members are gram-negative aerobic coccobacilli, is often isolated from water environments worldwide (1). This species has become increasingly important in recent years as a natural reservoir of antimicrobial resistance (AMR) genes (2)(3)(4)(5)(6). Acinetobacter baumannii, a cause of opportunistic infections in humans, has acquired resistance mechanisms to various antimicrobials, including clinically important carbapenems, making antimicrobial therapy di cult (7).…”
Section: Main Textmentioning
confidence: 99%
“…AMR genes, such as those for carbapenem-hydrolyzing enzymes (carbapenemases), have spread among environmental and clinical Acinetobacter species via mobile gene elements such as plasmids (2)(3)(4). Tigecycline is a last-resort antimicrobial with promising activity against carbapenemaseproducing gram-negative bacteria, including Acinetobacter species; however, mobile genes for tigecyclineinactivating enzymes, tet(X), have also emerged in A. towneri (5,6) and A. baumannii (8)(9)(10). Accumulation of such clinically relevant AMR genes in environmental bacteria such as A. towneri and their transmission to human pathogenic bacteria such as A. baumannii poses a global public health threat.…”
Section: Main Textmentioning
confidence: 99%